Tuberculosis susceptibility and protection in children. Issue 3 (March 2019) - Basu Roy, Robindra; Whittaker, Elizabeth; Seddon, James A; Kampmann, Beate
Summary: Children represent both a clinically important population susceptible to tuberculosis and a key group in whom to study intrinsic and vaccine-induced mechanisms of protection. After exposure to Mycobacterium tuberculosis, children aged under 5 years are at high risk of progressing first to tuberculosis infection, then to tuberculosis disease and possibly disseminated forms of tuberculosis, with accompanying high risks of morbidity and mortality. Children aged 5–10 years are somewhat protected, until risk increases again in adolescence. Furthermore, neonatal BCG programmes show the clearest proven benefit of vaccination against tuberculosis. Case-control comparisons from key cohorts, which recruited more than 15 000 children and adolescents in total, have identified that the ratio of monocytes to lymphocytes, activated CD4 T cell count, and a blood RNA signature could be correlates of risk for developing tuberculosis. Further studies of protected and susceptible populations are necessary to guide development of novel tuberculosis vaccines that could facilitate the achievement of WHO's goal to eliminate deaths from tuberculosis in childhood.